CompTIA Cloud+ (CV0-003) - Wong, Ronnie; Bryan, Wes (Packt Publishing, 2023)
This course begins with an introduction to the pivotal role of cloud computing in modern IT. Exploring beyond basic data storage and processing, it covers scalability, security, and various deployment models, providing an all-encompassing view of the cloud environment. Structured as an engaging journey, the course delves into the deployment and service models, emerging cloud technologies, and strategies for business and performance capacity planning. It emphasizes high availability, scalability, and effective use of regions and availability zones. You'll navigate through the complexities of Identity and Access Management (IAM), network security, and data protection, underlining the critical aspect of security in cloud computing. Practical demonstrations and hands-on exercises include resource provisioning, virtual machine deployment, and container configuration, ensuring real-world applicability. Towards the end, the course focuses on optimizing and maintaining cloud environments, with insights into automation, orchestration, and operational management. Completing this course equips you for the CompTIA Cloud+ certification and empowers you to manage and secure cloud environments, staying abreast of evolving technologies and threats. What you will learn Master Cloud deployment models Explore emerging Cloud technologies Plan for business capacity Implement high availability strategies Secure Cloud traffic effectively Deploy and configure containers Audience This course is tailored for IT professionals, system administrators, and network engineers aiming for CompTIA Cloud+ certification. It is ideal for tech leaders and project managers overseeing cloud projects, and aspiring cloud experts seeking in-depth knowledge in cloud deployment, security, and management. Perfect for those in technical roles needing a comprehensive understanding of cloud computing essentials. About the Authors ACI Learning: ACI Learning train leaders in Cybersecurity, Audit, and Information Technology. Whether you're starting your IT career, mastering your profession, or developing your team, they're with you every step of the way. Ronnie Wong: Ronnie brings over 20 years of experience in the field of computers and technology, coupled with more than a decade dedicated to technical instruction. This extensive background is complemented by an impressive array of certifications: Microsoft Certified Solutions Associate (MCSA), Microsoft Certified Technology Specialist (MCTS), and CompTIA's A+, Security+, Network+. Ronnie is also a certified IT Technician, holding the CCNA Security. Wes Bryan: Wes Bryan, our Edutainer, began his IT journey in 2009 and transitioned into IT instruction. He earned global teaching awards three times during his early teaching years and holds certifications including CompTIA A+, Network+, Security+, Server+, Cloud+, CySA+, MCSA, MTA, MCTS, MCP, MS, and MCT.
Online resource; title from title details screen (O'Reilly, viewed Decenber 19, 2023)
Keywords: Cloud computing -- Study guides -- Examinations; Microcomputers -- Study guides -- Maintenance and repair -- Examinations; Computer technicians -- Study guides -- Certification -- Examinations; Telecommunications engineers -- Study guides -- Certification -- Examinations; Infonuagique; Examens; Guides de l'étudiant; Micro-ordinateurs; Entretien et réparations; Examens; Guides de l'étudiant; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet